Attitudes of Poverty Aid Recipients in Kelurahan Melayu Kota Piring - Rahmawati, Nanik; Solina, Emmy; Elsera, Marisa; Wahyuni, Sri; Anggriawan, Dedi (Universitas Sebelas Maret, 2021)
This study aims to analyze the attitude of the community in terms of receiving poverty assistance. This research was conducted because it was found in the community that the number of people who were helped by looking at the integrated basic data (BDT) did not decrease even though the assistance provided was numerous and varied. UDB is used as a basis for disbursing government assistance to reduce poverty. Including, the poverty rate shows that there is no significant reduction in the poverty rate, and even tends to remain unchanged. The names of the same beneficiaries always appear from year to year. This study aims to determine how the attitude of the community in receiving the assistance. Using qualitative methods, it is used to analyze the attitudes of recipients of poverty assistance. some people still survive as recipients of poverty assistance, even though they are economically capable, and continue to remain in active status in the government database.